Measuring the Green Advertising Effectiveness of Cosmetic Products Using the AISAS Model - Salsabila, Jihan Aliya; Ali, Suprihatin; Septiani, Winda (PT. Riset Press International, 2025)
This study is motivated by the increasing public awareness of environmental issues that encourage companies to adopt green marketing, including through green advertising strategies. This study aims to measure and explain the effectiveness of green advertising on The Body Shop cosmetic products using the Attention, Interest, Search, Action, Share (AISAS) model. In addition, the AISAS model was chosen because it is relevant in mapping consumer behavior in the digital era, which includes attention, interest, information search, purchasing actions, and sharing experiences. This study uses a descriptive quantitative approach, with a survey method through a questionnaire distributed to 100 respondents. The sampling technique uses a non-probability method with a purposive sampling type. Data were analyzed using SPSS 27 and MS Excel software. The results show that green advertising of The Body Shop cosmetic products is considered effective in influencing consumers with an overall average score of 4.02, which is in the